O particípio presente no português antigo - Fiéis, Alexandra (2016)
This paper describes the behavior of present participles in a corpus of Old Portuguese and it raises some hypotheses concerning their syntactic status, compared to other non-finite forms. Although present participles in contemporary Portuguese no longer exist as verbal forms, in Old Portuguese we could find verbal occurrences of this form. In Old Portuguese, present participles could occur in typical adjectival contexts, while still maintaining verbal properties. Although there is some overlapping between present participles and gerunds, we argue that the functional structure of present participle clauses is more defective than the functional structure of gerund clauses.